Internal Carotid Artery Stenting in Patients with Near Occlusion: 30-Day and Long-Term Outcome - González, A.; Gil-Peralta, A.; Mayol, A.; Gonzalez-Marcos, J.R.; Moniche, F.; Aguilar, M.; Gutierrez, I. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: The natural history of the carotid NO is poorly characterized, and the management of patients remains controversial. We report the results and complications associated with CAS and follow-up. MATERIALS AND METHODS: Between March 2000 and March 2009, 116 of 836 CAS procedures were performed in patients with carotid NO (13.9%). A total of 99 men (85.3%) and 17 women (14.7%) with a mean age of 65.8 years were included. Presenting symptoms were TIA in 44 patients (37.9%) and minor stroke or noninvalidating stroke in 61 (52.6%). One hundred five patients (90.5%) were symptomatic. RESULTS: A distal filter was used for cerebral protection in 92 patients (79.3%). Transient hemodynamic alterations were frequent during balloon inflation: hypotension (37.1%), bradycardia (48.3%), and asystole in 24.1%. Four patients (3.4%) developed a TIA after CAS. Stroke in progression was arrested in the 1 patient (0.9%). The median follow-up period for patients was 36 months. Asymptomatic restenosis >70% occurred in 5 patients (4.3%); asymptomatic occlusion occurred in 3 patients (2.6%). During follow-up, 3 patients (2.6%) experienced a stroke, 1 ipsilateral (at 19 months) and 2 contralateral (at 6 and 30 months, respectively). Thirteen patients (11.2%) died, 7 from vascular causes. CONCLUSIONS: Our study showed that carotid NO is an under-recognized condition, and CAS would seem to be beneficial when performed by an experienced neurointerventional team. AcomAanterior communicating arteryCAScarotid angioplasty and stent placementCEAcarotid endarterectomyECSTEuropean Carotid Surgery TrialICAinternal carotid arterymRSmodified Rankin ScaleNASCETNorth American Symptomatic Carotid Endarterectomy TrialNNTnumber needed to treatNOnear occlusionPcomAposterior communicating arteryPTApercutaneous transluminal angioplastyTIAtransient ischemic attack